Expression and Function of the Testis-Predominant Protein LYAR in Mice - Lee, Boyeon (Korea Society for Molecular and Cellular Biology, 2013)
Mammalian spermatogenesis is a complex process involving an intrinsic genetic program of germ cell-specific and-predominant genes. In the present study, we analyzed the Ly-1 reactive clone (Lyar) gene in the mouse. Lyar, which is known to be expressed abundantly in the testis, encodes a nucleolar protein that contains a LYAR-type C2HC zinc finger motif and three nuclear localization signals. We herein confirmed that Lyar is expressed predominantly in the testis, and further showed that this expression is specific to germ cells. Protein analyses with an anti-LYAR antibody demonstrated that the LYAR protein is present in spermatocytes and spermatids, but not in sperm. To assess the functional role of LYAR in vivo, we used a gene-trap mutagenesis approach to establish a LYAR-null mouse model. Lyar mutant mice were born live and developed normally. Male mutant mice lacking LYAR were fully fertile and showed intact spermatogenesis. Taken together, our results demonstrate that LYAR is strongly preferred in male germ cells, but has a dispensable role in spermatogenesis and fertility.